2005
DOI: 10.1037/0735-7028.36.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Psychological Help Seeking in Clinical and Counseling Psychology Graduate Students.

Abstract: Psychologists are often called upon to provide supervision, mentorship, and training to graduate student therapists-in-training. In these roles, psychologists may influence whether graduate students enter personal therapy during their training. This study investigated variables (including perceived faculty attitudes about students in personal therapy) that predict psychotherapy help seeking in clinical and counseling psychology graduate students (N = 262). The findings indicated that confidentiality issues, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 30 publications
5
69
1
2
Order By: Relevance
“…Preliminary evidence has been helpful in reflecting and validating both the need for a systematic PPD approach within the Course (as highlighted by the trainees' concerns regarding the stressors of their role), as well as the intended value of, and areas for further consideration within, the current PPD methods. For example, specific attention can now be directed towards promoting the buddy system, and in general towards facilitating a positive attitude towards help-seeking behaviour (Dearing, Maddux, & Tangney, 2005). On the basis of feedback and trainees' essays on their understanding of PPD, it appears that the PPD model is relatively successful in making the links explicit between the various components of the course and the experiential learning cycle, promoting a person-centred framework for trainee development.…”
Section: Discussionmentioning
confidence: 97%
“…Preliminary evidence has been helpful in reflecting and validating both the need for a systematic PPD approach within the Course (as highlighted by the trainees' concerns regarding the stressors of their role), as well as the intended value of, and areas for further consideration within, the current PPD methods. For example, specific attention can now be directed towards promoting the buddy system, and in general towards facilitating a positive attitude towards help-seeking behaviour (Dearing, Maddux, & Tangney, 2005). On the basis of feedback and trainees' essays on their understanding of PPD, it appears that the PPD model is relatively successful in making the links explicit between the various components of the course and the experiential learning cycle, promoting a person-centred framework for trainee development.…”
Section: Discussionmentioning
confidence: 97%
“…As willingness to seek help is related to actual help seeking in the general population, 41 the RWP survey responses are a good indicator of future behavior. The rate of RWP utilization at our institution was 5% of trainees in 2004-2005 and 12% of trainees in 2009-2010.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study of 262 United States counseling psychology graduate students found that perceived barriers to personal therapy included cost, time, and confidentiality concerns (Dearing, Maddux, & Tangney, 2005). Seeking therapy was associated with year in the training program, believing that therapy was necessary to training, having positive attitudes towards help seeking, and concerns about confidentiality.…”
Section: Perceived Importancementioning
confidence: 96%